Photodynamic Therapy Can Modulate the Nasopharyngeal Carcinoma Microenvironment Infected with the Epstein–Barr Virus: A Systematic Review and Meta-Analysis - Fornel, Diógenes Germano [UNESP]; Ferrisse, Túlio Morandin [UNESP]; de Oliveira, Analú Barros [UNESP]; Fontana, Carla Raquel [UNESP] (MDPI, 2023)
Nasopharyngeal carcinoma is a malignancy from epithelial cells predominantly associated with the Epstein–Barr virus (EBV) infection, and it is responsible for 140,000 deaths annually. There is a current need to develop new strategies to increase the efficacy of antineoplastic treatment and reduce side effects. Thus, the present study aimed to perform a systematic review and meta-analysis of the ability of photodynamic therapy (PDT) to modulate the tumor microenvironment and PDT efficacy in nasopharyngeal carcinoma treatment. The reviewers conducted all steps in the systematic review. PubMed, Science Direct, Scopus, Scielo, Lilacs, EMBASE, and the Cochrane library databases were searched. The OHAT was used to assess the risk of bias. Meta-analysis was performed with a random-effects model (α = 0.05). Nasopharyngeal carcinoma cells treated with PDT showed that IL-8, IL-1α, IL-1β, LC3BI, LC3BII, MMP2, and MMP9 levels were significantly higher than in groups that did not receive PDT. NF-ĸB, miR BART 1-5p, BART 16, and BART 17-5p levels were significantly lower in the PDT group than in the control group. Apoptosis levels and the viability of nasopharyngeal carcinoma cells (>70%) infected with EBV were effective after PDT. This treatment also increased LMP1 levels (0.28–0.50/p < 0.05) compared to the control group. PDT showed promising results for efficacy in killing nasopharyngeal carcinoma cells infected with EBV and modulating the tumor microenvironment. Further preclinical studies should be performed to validate these results.
Keywords: Epstein–Barr virus; meta-analysis; nasopharyngeal carcinoma; photodynamic therapy; systematic review